The Medial Opening Wedge Osteotomy in Which The Tibial Tubercle Remains Attached to the Proximal Fragment: An Anatomıc Study (Annals of Medical Research, 2021)
None
Keywords: Proximal Tibial Osteotomy, High Tibial Osteotomy, Retrotubercle Osteotomy, Patella İnfera, Patella Baja, Anatomic Experiment